Legal-Philosophical Dimensions of Social Justice and Utilitarianism in Determining the Regional Minimum Wage of Banten Province - Ahmad Zaini; Sholahuddin Al Ayubi; Arif Rahman; Entol Zaenal Muttaqin; Ida Mursidah; Nita Anggraeni (Jurnal Hukum, 2025)
This study examines the extent to which the Provincial Minimum Wage embodies legally and philosophically grounded principles, including fair equality of opportunity, the difference principle, and the promotion of collective welfare. The study critically evaluates the 2025 Provincial Minimum Wage (UMP) policy in Banten, Indonesia, by examining its alignment with principles of normative justice, particularly Rawlsian distributive justice and utilitarian welfare maximization, alongside workers’ perceptions of wage adequacy and fairness. Using a mixed-methods approach that combines critical-philosophical analysis with descriptive quantitative techniques, the study integrates normative assessments of wage regulations, including Governor Decree Number 456/Kep.292-Huk/2024 and relevant labor laws, with survey data from 103 formal sector workers in Banten. The findings reveal a persistent gap between the policy’s objectives and worker’ lived experiences. From a Rawlsian perspective, the policy under-benefits the most economically vulnerable groups, while a utilitarian analysis suggests that the current system does not fully maximize collective welfare. Many respondents considered their wages insufficient for basic living expenses, with incentives and bonuses lacking transparency.